Pengaruh Perilaku Merokok Terhadap Kejadian Acne Vulgaris Pada Mahasiswa Universitas Yarsi Angkatan 2023 - Rafi Syahriza; Zakiyah; Edward Syam (Syntax Idea)
Acne vulgaris is a chronic inflammatory disease commonly found in areas with sebaceous glands, often leaving scars that affect quality of life. One of the health challenges in Indonesia is the high number of smokers, the largest in Southeast Asia. Cigarettes expose individuals to various chemical substances, including reactive oxygen species, carbon monoxide, reactive nitrogen, and electrophilic aldehydes. Exposure to carbon monoxide can reduce blood oxygen levels and impair blood circulation throughout the body, including the skin. Reduced skin oxygenation can inhibit skin cell regeneration, increase the likelihood of inflammation, and lead to acne vulgaris. To determine the relationship between smoking and the increased prevalence of acne vulgaris. This quantitative study employed an observational analytic approach with a cross-sectional design. The sampling was done using a purposive random sampling technique, involving a total of 84 students. Data were collected using primary data from questionnaires. The statistical analysis used included univariate analysis and bivariate analysis with Fisher's exact test. The study showed a significant relationship between the number of cigarettes smoked and acne vulgaris, with a p-value <0.001 (p>0.05). However, there was no significant relationship between the duration of smoking and the incidence of acne vulgaris, with a p-value of 0.288 (p>0.05). There is a relationship between the number of cigarettes smoked and acne vulgaris. However, there is no relationship between the duration of smoking and the condition.